Rancang Bangun Sistem Informasi Peminjaman Ruangan (SIPINRU) Berbasis Web Menggunakan Metode Waterfall - Kunti Inayati; Wibowo, Susilo Setyo Tri; Pamungkas, Jordan Ramadani; Chotijah, Umi (Jurnal Sistem Informasi Komputer ( SIKOM ), 2026)
Room management plays an important role in supporting academic and non-academic activities in higher education institutions. This study aims to design and develop a web-based Room Loan Information System (SIPINRU) that facilitates the room borrowing process in a more efficient and transparent manner. The system is developed using the PHP programming language with MySQL as the database and applies the Waterfall development method. SIPINRU allows students and lecturers to submit room loan requests online without requiring prior login, making the submission process simpler and more accessible. In addition, the application provides real-time updates on the submission status, enabling applicants to quickly obtain clear information regarding approval or rejection without prolonged waiting times. Administrators are responsible for managing room data and verifying loan requests through the system. Black box testing results indicate that all system functions operate as expected according to the defined requirements. Therefore, SIPINRU is expected to improve the effectiveness of room loan management in higher education environments.